2017
DOI: 10.1080/09540105.2017.1347148
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activities of phenolic compounds isolated from Melipona beecheii honey

Abstract: Methanolic extract was obtained from Melipona beecheii honey and quantitative analysis of components like total amount of phenolic compounds, flavonoids and flavonols were estimated. Phenolic acids and flavonoids were fractionated by reverse phase HPLC and assessed for antioxidant and anti-inflammatory activities by in vitro methods. Total phenol content was estimated as 63.22 mg of Gallic acid equivalents/100 g of honey. Total flavonoids and flavonols were found to be 3.61 and 3.16 mg of Catechin or Naringeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 25 publications
2
75
0
1
Order By: Relevance
“…The secondary metabolite content of the arabica coffee ground nanoparticles are alkaloids, saponins, and phenolics, with a total phenolic content of 1246.897 µ g GAE/g. Phenolic compounds are compounds providing antioxidant and anti-inflammatory effects [29][30][31][32][33][34]. A nano-sized active drug has the advantage of being able to pass through cell walls and membranes to reach the target cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary metabolite content of the arabica coffee ground nanoparticles are alkaloids, saponins, and phenolics, with a total phenolic content of 1246.897 µ g GAE/g. Phenolic compounds are compounds providing antioxidant and anti-inflammatory effects [29][30][31][32][33][34]. A nano-sized active drug has the advantage of being able to pass through cell walls and membranes to reach the target cell.…”
Section: Resultsmentioning
confidence: 99%
“…Arabica coffee ground nanoparticles have a phenolic content of 1246.897 µg GAE/g. The phenolic compounds in coffee have some bioactivities, such as antioxidant, antibacterial and anti-inflammatory activities [29,30,32,33,[41][42][43]. The total phenolic dosage of the coffee ground nanoparticles gel preparations ranged from 540.86 to 672.10 µg GAE/g ( Table 2).…”
Section: Total Phenolicmentioning
confidence: 99%
“…Many studies have demonstrated that food samples with high antioxidant activity also have implications on immune stimulation (Ruiz‐Ruiz, Matus‐Basto, Acereto‐Escoffié, & Segura‐Campos, ; Zhang, Hu, Jiang, Zhao, & Zhu, ). For this reason, we ascertained the effect of the samples on NO and TNF‐α production in PBMCs.…”
Section: Resultsmentioning
confidence: 99%
“…The reducing potential is commonly connected with the number of reductones in the test samples [4]. The chelating capacity is essential to determine the antioxidant power of crude extract or single compound because it decreases the number of metal ions by catalyzing malondialdehyde [51]. The antioxidant activity of the CuO NPs (3 mg/L) elicited CSC extracts was higher (80.55 mg/g) than non-elicited CSC extracts (69.50 mg/g) (Figure 4c).…”
Section: Antioxidant Activitymentioning
confidence: 99%